Linked : how everything is connected to everything else and what it means for business, science, and everyday life - e uthor (2014)
"Albert-Laszlo Barabasi, the nation's foremost expert in the new science of networks, takes us on an intellectual adventure to prove that social networks, corporations, and living organisms are more similar than previously thought. A full understanding of network science will someday enhance our ability to design blue-chip businesses, stop the outbreak of deadly diseases, and influence the exchange of ideas and information. Engaging and authoritative, Linked provides an exciting glimpse into the next century of science and an urgent new perspective on our interconnected world. Book jacket."--
Introduction -- The random universe -- Six degrees of separation -- Small worlds -- Hubs and connectors -- The 80/20 rule -- Rich get richer -- Einstein's legacy -- Achilles' heel -- Viruses and fads -- The awakening Internet -- The fragmented web -- The map of life -- Network economy -- Web without a spider -- Afterlink: Hierarchies and communities.
First published by Perseus in 2002.
Includes bibliographical references (p. 243-279) and index.
Keywords: System theory; Science -- Philosophy; Computer networks -- Miscellanea; Social networks -- Miscellanea; Economics -- Miscellanea; World Wide Web -- Miscellanea; Computer networks; Economics; Science -- Philosophy; Social networks; System theory; World Wide Web; Miscellanea